Homology modeling, vasorelaxant and bradykinin-potentiating activities of a novel hypotensin found in the scorpion venom from Tityus stigmurus. (July 2015) - Machado, Richele J.A.; Junior, Leônidas G.M.; Monteiro, Norberto K.V.; Silva-Júnior, Arnóbio A.; Portaro, Fernanda C.V.; Barbosa, Euzébio G.; Braga, Valdir A.; Fernandes-Pedrosa, Matheus F.
Abstract: In a recent work by our group involving a transcriptomics approach applied to the venom glands from Tityus stigmurus we identified a new family of peptides called Hypotensins (TSTI0006C) (Almeida et al., 2012). The cluster TSTI0006C was analyzed in the main 25 amino acid residues and named T. stigmurus Hypotensin (TistH), showing a molecular mass of 2.7 kDa, an absence of cysteines and the presence of two C-terminal proline residues, which are a bradykinin-potentiating peptide (BPP) signature. Here, we describe the homology modeling of the three-dimensional structure of TistH. In addition, we evaluated the cardiovascular effects elicited by TistH in normotensive rats. Firstly, TistH showed no cytotoxic effect on horse erythrocyte. Furthermore, in normotensive rats TistH was able to potentiate the hypotensive action of bradykinin (BK) and induced a vasorelaxant effect in mesenteric artery rings by endothelium-dependent release of nitric oxide (NO) and demonstrated independent inhibition of angiotensin converting enzyme (ACE). Our data can contribute to a better understanding of the structural and functional characteristics of TistH and suggest its potential use in cardiovascular diseases. Highlights: TistH is a new hypotensin deduced from the transcriptome of Tityus stigmurus venom gland. A three-dimensional structure of TistH was generated by modeling and dynamics simulations. The cardiovascular effect of TistH was demonstrated. The results can aid the development of new classes of antihypertensive peptides.